Pengaruh Digitalisasi Operasional dan Integrasi Rantai Pasok Terhadap Keberlanjutan Usaha pada Supplier Karkas Unggas Bebek Ndeso di Wonogiri - Dimas Ridlo Wicaksono; Harsanto Harsanto; Nur Hadi (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
The dynamics of the agribusiness sector demand that SMEs agilely adapt to technology while maintaining solid coordination within their network of partners and consumers. Driven by this urgency, this study aims to investigate the effect of operational digitalization on supply chain integration, as well as to examine the impact of these variables on business sustainability in the poultry carcass supplier Bebek Ndeso Wonogiri. This study employs a quantitative approach with a survey design, involving 70 respondents consisting of internal and external parties through a purposive sampling technique. Primary data were collected using a Likert scale 1–5 structured questionnaire and analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) based on SmartPLS 4. Based on the data processing results, it is revealed that operational digitalization has a positive and significant effect in establishing reliable supply chain integration, which in turn is proven to have a positive and significant effect on enhancing business sustainability. On the other hand, operational digitalization was recorded as not having a direct significant effect on business sustainability. Substantively, these findings conclude that achieving business sustainability in the poultry carcass industry does not solely rely on technological modernization, but is heavily influenced by the effectiveness of supplier coordination, internal workflow synchronization, and the quality of customer relations. The implication of these findings underscores the importance for business actors to combine the use of digital technology with a comprehensive supply chain integration strategy in order to secure long-term business continuity.